The Analysis of the Influence of Sustainability Reports on Firm Value With Company Size as Moderation - Setioningsih, Retno; Budiarti, Laeli (Faculty of Economics and Business, Jenderal Soedirman University, 2024)
This study aims to analyze and obtain empirical evidence of the effect of disclosure sustainability performance on firm value and the effect of disclosure sustainability performance on firm value moderated by firm size. This study uses annual report data of the mining industry sector companies from period 2015 to 2019. The sample in this study is 15 mining companies listed on the Indonesia Stock Exchange (IDX). Total data to be analized are 75. Firm value is measured by price to book value (PBV), sustainability performance is measured by GRI-G4 items and firm size is measured by dummy 0 and 1. The data is processed using Partial Least Square. The analysis consist of descriptive statistics, inner model evaluation analysis, direct effect significance test and moderating effect significance test. The result found that the extent of sustainability performance has a negative effect on firm value and the firm size is moderate the relationship between sustainability performance and firm size. The implication of this research gives information to companies to contribute to increasing the value of the company by paying attention to sustainability performance disclosure. Large or small companies are required to disclosure sustainability performance.